2010
DOI: 10.1111/j.1365-2761.2010.01207.x
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of indices of gross pathology associated with the nematode Anguillicoloides crassus in eels

Abstract: This study compares two alternative indices for quantifying the gross pathology of the swimbladder of eels, Anguilla anguilla (L.), infected with the nematode Anguillicoloides crassus. Two observers recorded twice the scores obtained by the two indices on the same set of 71 wild caught eels (from elver to silver eels, French Mediterranean lagoons). The Length Ratio Index (LRI), performed better than the Swimbladder Degenerative Index (SDI), in three of four predefined criteria of decision. First, the LRI bette… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 42 publications
(61 reference statements)
1
18
1
Order By: Relevance
“…Moreover, we recently demonstrated a very strong association between the severity in the SDI scores and the functional loss in swimbladder gas volume, thereby definitively validating the biological significance of the index [25]. For statistical reasons (i.e.…”
Section: (C) Factors Describing Past and Current Infectionsmentioning
confidence: 53%
See 1 more Smart Citation
“…Moreover, we recently demonstrated a very strong association between the severity in the SDI scores and the functional loss in swimbladder gas volume, thereby definitively validating the biological significance of the index [25]. For statistical reasons (i.e.…”
Section: (C) Factors Describing Past and Current Infectionsmentioning
confidence: 53%
“…In the case of anguillicolosis, we suggest that the only realistic way to resolve the observed paradox (i.e. greater size/better condition among severely affected eels, observed in this and other studies) is to combine mark -recapture sampling with echo/radio imagery techniques to non-invasively assess the swimbladder condition among tagged eels (for reliability and applicability; [25,64]). Therefore, we call for scientists and eel managers to consider integrating an epidemiological dimension into their long-term monitoring programmes.…”
Section: Resultsmentioning
confidence: 85%
“…Nevertheless, using the Swimbladder Degenerative Index, Lefebvre et al [44] recently demonstrated that the most affected eels had greater body length and mass (+11% and +41% respectively) than unaffected eels of the same age. Despite these surprising counterintuitive results, high virulence and severe impacts of A. crassus are expected because A. anguilla lacks an adaptive immune response, and various pathogenic potentially lethal effects (e.g., anemia, energy drain, swimming performance decrease) have been demonstrated, threatening the success of spawning migration in the Sargasso Sea [35, 43, 44, 53, 58]. …”
Section: Discussionmentioning
confidence: 99%
“…Following Székely et al (2005), we computed the infection level as the ratio between the parasite total weight and the eel weight (Wp/ W). The relative swim bladder length or Length Ratio Index (LRI), computed as the ratio between the swim bladder length and the eel length (Ls/L), was used for establishing the degree of the mechanical swim bladder damage: the smaller LRI, the higher the damage (Lefebvre et al 2011). …”
Section: Parasitology Investigationmentioning
confidence: 99%